1993
DOI: 10.1159/000187399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hemodialysis on Plasma Levels of Vasoactive Peptides: Endothelin, Calcitonin Gene-Related Peptide and Human Atrial Natriuretic Peptide

Abstract: To determine the role of vasoactive peptides such as endothelin (ET), calcitonin gene-related peptide (CGRP) and human atrial natriuretic peptide (hANP) in the regulation of blood pressure in uremic patients, and to determine the effect of various types of dialyzer membranes on hemodialysis (HD)-induced changes in plasma levels of such peptides, plasma ET, CGRP and hANP were measured in HD patients and patients on continuous ambulatory peritoneal dialysis (CAPD). Plasma levels of ET, CGRP, and hANP were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1

Year Published

1995
1995
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 14 publications
3
21
1
Order By: Relevance
“…In agreement with an earlier report by Koyama et al [4], others have also found a decrease in plasma ET-1 concentrations on hemodialysis [7, 8], in contrast to those who reported unchanged [5, 11, 13]or even increased [14]plasma ET-1 after a hemodialysis session. In addition, it was not clarified whether volume loss associated with ultrafiltration or hemodialysis is responsible for changes in plasma ET-1 associated with hemodialysis [11, 13, 14, 15, 16]. …”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with an earlier report by Koyama et al [4], others have also found a decrease in plasma ET-1 concentrations on hemodialysis [7, 8], in contrast to those who reported unchanged [5, 11, 13]or even increased [14]plasma ET-1 after a hemodialysis session. In addition, it was not clarified whether volume loss associated with ultrafiltration or hemodialysis is responsible for changes in plasma ET-1 associated with hemodialysis [11, 13, 14, 15, 16]. …”
Section: Introductionsupporting
confidence: 92%
“…Since they studied an unselected group of ESRF subjects it is likely that both normotensives and hypertensives were included, all the more because 8 out of their 16 subjects had left ventricular hypertrophy on echocardiography. For the same reason, namely the lack of division of the study group on the basis of blood pressure values, we are not able to comment on the lack of effect of isolated ultrafiltration through non-high-flux dialyzers on plasma ET-1 reported by Peco-Antic et al [15]in children and by Niwa et al [11]in adults. However, that Peco- Antic et al [15]reported that isolated hemodialysis produced more pronounced rises in the children with hypertrophied left ventricle (and presumably with hypertension), is not totally discordant with our finding of elevated plasma ET-1 in hypertensives after the first protocol stage.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This may explain the differences observed between peritoneal dialysis (CAPD) and no dialysis on the one hand and haemodialysis on the other, although this is controversial [46,58]. High-flux membranes (PAN, PMMA, CTA) seem to clear endothelin better than normal membranes [61]. Whether these findings reflect a pathogenetic role for endothelin in chronic renal disease in humans will be clarified by appropriate clinical studies with endothelin antagonists in the future.…”
mentioning
confidence: 99%